Stem‐cell mobilization of healthy sibling donors with pegfilgrastim—A prospective open‐label phase II trial (EudraCT no: 2005‐004971‐39). Issue 1 (10th December 2021) - Vucinic, Vladan; Jentzsch, Madlen; Leiblein, Sabine; Bach, Enrica; Remane, Yvonne; Schulze‐Forster, Kai; Cross, Michael; Pönisch, Wolfram; Schwind, Sebastian; Franke, Georg‐Nikolaus; Platzbecker, Uwe; Niederwieser, Dietger
Abstract: Background: Pegfilgrastim is a covalently bound conjugate of filgrastim and mono‐methoxypolyethylene glycol with a longer half‐life. Study Design and Methods: We report on phase II prospective monocentric trial examining the feasibility of stem cell mobilization with 12 mg single dose pegfilgrastim in related donors. The objectives were to determine the optimal collection day, defined as CD34+ concentration in peripheral blood (PB) >50 cells/μl, the number of donors collected with single leukapheresis, and the peak level of pegfilgrastim in donor‐serum. Furthermore, the cell composition of grafts was assessed and compared to published data. Results: The results included about 28 matched related donors. The median pegfilgrastim serum level remained >200 ng/mL for 48 hours before declining, with the maximal measured concentration of 259.49 ng/ml 24 h after application. The median white blood cell count and CD34 count in PB peaked on day four with 52.6 (range 22.8–85.0) Gpt/l and 66.25 (range 22.9–136.6) cells/μl, respectively. A CD34+ count >50 cells/μl on day four was detected in 75% of donors. 79% of the donors underwent a single collection. Conventional filgrastim was administered additionally in two donors, due to insufficient CD 34+ concentration in PB. 89% of donors showed CD34+ yields ≥4 (median 6.5, range 4.6–14.5) × 10/kg body weight of the recipient. All grafts were administered without rejections. Discussion: The results of this trial showed that stem cell mobilization with pegfilgrastim is a feasible, and attractive option. This is the first trial presenting the kinetics of pegfilgrastim serum levels in healthy donors.